Surfactant-free co-solvent exfoliation strategy for semiconducting quasi-1D Nb2Pd3Se8 nanowires - Choi, Kyung Hwan; Kim, Yeongjin; Kang, Jinsu; Kim, Kyung In; Park, Jeong Su; Oh, Hyung Suk; Yu, Hak Ki; Choi, Jae Young (CrystEngComm, 2025)
Nb2Pd3Se8, a quasi-one-dimensional (1D) van der Waals material, has recently gained attention owing to its intriguing structural, electrical and optoelectrical properties. In this work, we studied co-solvent exfoliation of Nb2Pd3Se8 in a mixture of water and ethanol or isopropanol. By adjusting the compositions of the co-solvent, the dispersion behavior of Nb2Pd3Se8 was interpreted in terms of surface tension and dielectric constant. This approach is effective for substituting the previously reported optimal solvent of NMP, which is toxic with a high boiling point of 204 °C. The Nb2Pd3Se8 nanowire prepared through co-solvent exfoliation presented a high electronic property with an electron mobility of 10.3 cm2 V−1 s−1
Keywords: Cosolvents; Dispersion behavior; Isopropanol; Optimal solvents; Optoelectrical properties; Quasi-one dimensional; Quasi-one-dimensional; Solvent exfoliations; Surfactant-free; Van der Waal